Ascorbate-glutathione cycle in wheat and rice seedlings under anoxia and subsequent reaeration - V. V. Yemelyanov; E. G. Prikaziuk; V. V. Lastochkin; O. M. Aresheva; T. V. Chirkova (Вавиловский журнал генетики и селекции)
The most important part of the plant antioxidant system is the ascorbate-glutathione cycle (AGC), the activity of which is observed upon exposure to a range of stressors, including lack of O2, and oxidative stress occurring immediately after the restoration of oxygen access, hereafter termed reaeration or post-anoxia. The operation of the AGC (enzymes and low-molecular components) in wheat (Triticum aestivum, cv. Leningradka, non-resistant to hypoxia) and rice (Oryza sativa, cv. Liman, resistant) seedlings after 24 h anoxia and 1 h or 24 h reaeration was studied. Significant accumulation of oxidized forms of ascorbate and glutathione was revealed in the non-resistant plant (wheat) after 24 h of anoxia and reaeration, indicating the development of oxidative stress. In the resistant plant (rice), reduced forms of these antioxidants prevailed both in normoxia and under stress, which may indicate their intensive reduction. In wheat, the activities of ascorbate peroxidase and dehydroascorbate reductase in shoots, and monodehydroascorbate reductase and glutathione reductase in roots decreased under anoxia and reaeration. The activity of antioxidant enzymes was maintained in rice under lack of oxygen (ascorbate peroxidase, glutathione reductase) and increased during post-anoxia (AGC reductases). Anoxia stimulated accumulation of mRNA of the organellar ascorbate peroxidase genes OsAPX3, OsAPX5 in shoots, and OsAPX3-5 and OsAPX7 in roots. At post-anoxia, the contribution of the OsAPX1 and OsAPX2 genes encoding the cytosolic forms of the enzyme increased in the whole plant, and so did that of the OsAPX8 gene for the plastid form of the enzyme. The accumulation of mRNA of the genes OsMDAR2 and OsMDAR4 encoding peroxisomal and cytosolic monodehydroascorbate reductase as well as the OsGR2 and OsGR3 for cytosolic and organellar glutathione reductase was activated during reaeration in shoots and roots. In most cases, O2 deficiency activated the genes encoding the peroxisomal, plastid, and mitochondrial forms of the enzymes, and upon reaeration, an enhanced activity of the genes encoding the cytoplasmic forms was observed. Taken together, the inactivation of AGC enzymes was revealed in wheat seedlings during anoxia and subsequent reaeration, which disrupted the effective operation of the cycle and triggered the accumulation of oxidized forms of ascorbate and glutathione. In rice, anoxia led to the maintenance of the activity of AGC enzymes, and reaeration stimulated it, including at the level of gene expression, which ensured the effective operation of AGC.